If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(4z-1)=3(1z+2)
We move all terms to the left:
-2(4z-1)-(3(1z+2))=0
We add all the numbers together, and all the variables
-2(4z-1)-(3(z+2))=0
We multiply parentheses
-8z-(3(z+2))+2=0
We calculate terms in parentheses: -(3(z+2)), so:We get rid of parentheses
3(z+2)
We multiply parentheses
3z+6
Back to the equation:
-(3z+6)
-8z-3z-6+2=0
We add all the numbers together, and all the variables
-11z-4=0
We move all terms containing z to the left, all other terms to the right
-11z=4
z=4/-11
z=-4/11
| -4+3x=-2x+11 | | 6(3x+5)+5(4x+4)+2=38x+52 | | 7/8d=49 | | 2x-3+9=13 | | 4(5x+3)+2(2x+6)+4=24x+28 | | 2x+5x+7=49 | | 20x-6=21x+9 | | Z-5x=3x | | 2r-24=-3r+36 | | 2r-24=-3r+30 | | -9u-46=-4(u+9) | | 4-2x=-5x-8 | | -9(v+4)=-4v-1 | | 1.2+x+0.4=9.7 | | 5(v-5)-7v=-19 | | 3g-50=7g-34 | | 10-h=4h+20 | | 44,112+10.75x=22.75x | | 1+2 | | 1+2 | | -3x+39(4x-5)=21 | | 14x+122x-16=17(8x+13) | | x-3/4=3x-3 | | 6-(x-3)=4(x+9) | | 13t=12 | | 12x^2+17x+6=12x2+17x+6 | | 17r=10 | | 3x+48=9x-6 | | 4.6+10m=7.89 | | 4.6+10m=789 | | 8x+2=32-2x | | 6x+6x-3=3(4x+4 |